SINTESIS DAN UJI AKTIVITAS ANTIOKSIDAN SENYAWA 3-(4-METOKSIFENIL)-5-NAFTALEN-1-IL-1-FENIL-4,5-DIHIDRO-PIRAZOL - Aisyah, -; Jasril, -; Teruna, Hilwan Yuda (Sistem Informasi, 2017)
A pyrazoline analog, 3-(4-methoxy-phenyl)-5-naphtalen-1-yl-1-phenyl-4,5-dihydro-pyrazole (PF CA-4OMe) has been synthesized via intermolecular cyclization between substituted chalcones and phenylhydrazine using glacial acetic acid as a catalyst under microwave irradiation. The structure of the compound was characterized based on the interpretation of UV, FTIR, HRMS, 1H-NMR, 13C-NMR, HSQC and HMBC spectra. The antioxidant test was carried out by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The result show that PF CA-4OMe was proved to have antioxidant activity with IC50 387,64 Âµg/mL.